O zakonitem sorazmerju med starostnimi in drugimi sistemskimi lastnostmi frazeoloških enot - Polikarpov, Anatolij Anatol'evič (Slavistična revija, 2005)
The subject of the present study is the analysis of systemic correlations between some significant features of phraseological units (PU), i.e., their age, degree of polysemy, how idiomatic or, rather, semantically fused they are, semantic type (in terms of presence/absence od denotatively negative and subjectively negative elements in the meaning of the PU), the degree of applicability, features concerning the stylistic register, etc.
Keywords: frazeologija; phraseology; računalniška lingvistika; Slovene; slovenščina; statistika (lin.)